The Right of Access to Sufficient Water - Mbazira, Christopher (Economic and Social Rights in South Africa, 2007)
While the report provides valuable information on a number of positive developments in the provision of water services, it is deficient in a number of respects. The most visible deficiency is its lack of comprehensiveness and its failure to verify most of the information it relies on both to credit and discredit the government. It is argued that these deficiencies can be attributed to the sixth protocol on the right to water (the water protocol), which fails in some important respects to elicit information in ways that would allow a deeper analysis of the state’s performance.